Problematizing Fertility Decline Without Women’s Empowerment in Turkey - Him, M.S. (Emerald Group Publishing Ltd., 2017)
This chapter examines men’s involvement in birth control from a feminist political-economic perspective. Fertility, and hence women’s body, is still a focus of political struggles today. In the late 1990s, the international community of population policy recognized a concept of women’s reproductive rights and adopted a rights-based discourse in place of a language of economic efficiency. At the same time, they advocated for men’s participation in family planning and burden sharing between couples. This gender-sensitive new policy was effective in achieving more successful contraception in patriarchal societies where men are decision-makers in many aspects of social life. Yet, from a feminist perspective, such a policy could threaten women’s reproductive rights if gender relations remain patriarchal. A close examination of Turkey’s fertility decline suggests that the process was led by men who increasingly aspired to have small families which they could manage to look after as wage-earning fathers. In other words, it was realized without women’s empowerment. A case study of Kurdish women conducted in Eastern Turkey where fertility rate was significantly higher than the national average indicates a positive impact of men’s involvement on effective birth control. Yet this study also suggests a risk of undermining women’s empowerment and autonomy. The promotion of men’s involvement in family planning can reinforce men’s control over women’s bodies and endorse birth control without women’s empowerment again, unless it is consciously designed in the context of reproductive rights. © 2018 Emerald Publishing Limited.
Keywords: Birth Control; Empowerment; Fertility; Kurdish Women; Patriarchy; Turkey